Monitoramento genético da população Ex Situ da jacutinga (Aburria jacutinga, Aves, Cracidae) como subsídio para a conservação da espécie - Oliveira Junior, Paulo Roberto Ramos de (Universidade Federal de São Carlos, 2012)
Several critically endangered species and subspecies have been saved from extinction in recent years by Ex Situ conservation strategies. However, captive populations are generally small and exposed to the effects of genetic drift, inbreeding and founder effects. Thus, a major challenge for long-term reproduction of these animals is to reduce the loss of heterozygosity and of allelic diversity. The genetic management can guide the matings to maintain the genetic variation as high as possible in the population. It can be achieved by calculating the genetic distance between the specimens, which is performed using molecular biology techniques. The Black-fronted Piping-Guan, Aburria jacutinga (Aves, Cracidae), is an endemic bird of the Atlantic Forest that is threatened of extinction due to the drastic destruction of this biome and the heavy hunting pressure. Among the suggested conservation actions for this species are the development of an Ex Situ conservation program with the goal of making reintroductions in areas where it has become extinct, as well as the maintenance of these captivity stocks controlled by a studbook. Here we have genotyped and analyzed 146 individuals from the five main breeding facilities. The results demonstrated five genetically differentiated populations of Black-fronted Piping-Guan, but their levels of genetic variability were very similar. However when these levels are compared with other species, the data suggest that the genetic variation is lower than desirable to reach the objectives proposed by the Ex Situ conservation programs. Pairing tables and genetic rankings were constructed and indicated kinship and levels of genetic variability of each bird. It was possible to identify the best pairs to be mated and individuals that were adequate for reintroductions.
Keywords: Variabilidade genética; Aburria jacutinga; Aves - conservação; Ex Situ Conservation; Threatened Species; Atlantic Forest; Microsatellites; Genetic Variability; CIENCIAS BIOLOGICAS::GENETICA